2011
DOI: 10.3109/09537104.2011.603065
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide treatment reduces rat platelet aggregation independent of intracellular reactive-oxygen species generation

Abstract: High production of reactive-oxygen species (ROS) by blood cells is involved in damage of the vascular endothelium and multiple organ dysfunction in sepsis. However, little is known about the intraplatelet ROS production in sepsis and its consequences on platelet reactivity. In this study, we evaluated whether the treatment of rats with lipopolysaccharide (LPS) affects platelet aggregation through intraplatelet ROS generation. Rats were injected with LPS (1 mg/kg, i.p.), and at 2 to 72 h thereafter, adenosine d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 34 publications
0
23
1
5
Order By: Relevance
“…Regarding platelet function recent studies have negated the existence of a thrombocytopathy and demonstrated, conversely, that LC is associated with platelet hyperfunction; the underlying mechanism, however, is still to be elucidated. We speculated that, as for clotting system, low‐grade endotoxemia might represent a trigger for platelet activation as studies have demonstrated, even if not univocally, that bacterial lipopolysaccharides (LPS) triggers platelet activation . To explore this issue, we measured serum levels of LPS and two markers of platelet activation, soluble cluster of differentiation 40 ligand (sCD40L) and soluble p‐selectin (sPs), in a population with LC and in a control group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding platelet function recent studies have negated the existence of a thrombocytopathy and demonstrated, conversely, that LC is associated with platelet hyperfunction; the underlying mechanism, however, is still to be elucidated. We speculated that, as for clotting system, low‐grade endotoxemia might represent a trigger for platelet activation as studies have demonstrated, even if not univocally, that bacterial lipopolysaccharides (LPS) triggers platelet activation . To explore this issue, we measured serum levels of LPS and two markers of platelet activation, soluble cluster of differentiation 40 ligand (sCD40L) and soluble p‐selectin (sPs), in a population with LC and in a control group.…”
mentioning
confidence: 99%
“…We speculated that, as for clotting system, low-grade endotoxemia might represent a trigger for platelet activation as studies have demonstrated, even if not univocally, that bacterial lipopolysaccharides (LPS) triggers platelet activation. (10)(11)(12)(13) To explore this issue, we measured serum levels of LPS and two markers of platelet activation, soluble cluster of differentiation 40 ligand (sCD40L) and soluble p-selectin (sPs), in a population with LC and in a control group. Furthermore, we performed ex vivo study to evaluate platelet aggregation (PA) in response to subthreshold concentrations (STCs) of common agonists in platelets from cirrhosis patients and controls.…”
mentioning
confidence: 99%
“…Rats were injected intraperitoneally (ip) with saline (300 μL) or LPS (1 mg/kg), and 48 hours thereafter, arterial blood was collected, and washed platelets were obtained. This time of 48 hours post‐LPS injection was selected based on our previous experience showing a significant inhibition of ADP (10 μmol/L)‐induced platelet aggregation . Briefly, washed platelets were pre‐incubated for 15 minutes at 37°C with PP2 (inhibitor of Src family protein tyrosine kinases; 10 μmol/L), wortmannin (PI3K inhibitor; 100 nmol/L), API‐1 (Akt inhibitor; 20 μmol/L), GF109203X (PKC inhibitor; 10 μmol/L), ODQ (sGC inhibitor; 25 μmol/L), Rp‐8‐Br‐cGMPS (PKG inhibitor; 5 μmol/L) or vehicle (1% DMSO).…”
Section: Methodsmentioning
confidence: 99%
“…However, the signalling pathways that lead to intraplatelet ROS release are not completely understood. A study presented by our group showed that activated platelets of LPS‐treated rats release NADPH oxidase‐dependent ROS . Recently, we showed that PKG‐mediated inhibition of platelet aggregation by LPS treatment is modulated upstream by PKC and Akt .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation